Physiology of Methylotrophs Living in the Phyllosphere - Hiroya Yurimoto; Kosuke Shiraishi; Yasuyoshi Sakai (Microorganisms, 2021)
Methanol is abundant in the phyllosphere, the surface of the above-ground parts of plants, and its concentration oscillates diurnally. The phyllosphere is one of the major habitats for a group of microorganisms, the so-called methylotrophs, that utilize one-carbon (C1) compounds, such as methanol and methane, as their sole source of carbon and energy. Among phyllospheric microorganisms, methanol-utilizing methylotrophic bacteria, known as pink-pigmented facultative methylotrophs (PPFMs), are the dominant colonizers of the phyllosphere, and some of them have recently been shown to have the ability to promote plant growth and increase crop yield. In addition to PPFMs, methanol-utilizing yeasts can proliferate and survive in the phyllosphere by using unique molecular and cellular mechanisms to adapt to the stressful phyllosphere environment. This review describes our current understanding of the physiology of methylotrophic bacteria and yeasts living in the phyllosphere where they are exposed to diurnal cycles of environmental conditions.